Design and development an insect-inspired humanoid gripper that is structurally sound, yet very flexible - Hajjaj, S.; Pun, N.* (IOP Publishing, 2013)
One of the biggest challenges in mechanical robotics design is the balance between structural integrity and flexibility. An industrial robotic gripper could be technically advanced, however it contains only 1 Degree of Freedom (DOF). If one is to add more DOFs the design would become complex. On the other hand, the human wrist and fingers contain 23 DOFs, and is very lightweight and highly flexible. Robotics are becoming more and more part of our social life, they are more and more being incorporated in social, medical, and personal application. Therefore, for such robots to be effective, they need to mimic human performance, both in performance as well as in mechanical design. In this work, a Humanoid Gripper is designed and built to mimic a simplified version of a human wrist and fingers. This is attempted by mimicking insect and human designs of grippes. The main challenge was to insure that the gripper is structurally sound, but at the same time flexible and lightweight. A combination of light weight material and a unique design of finger actuators were applied. The gripper is controlled by a PARALLAX servo controller 28823 (PSCI), which mounted on the assembly itself. At the end, a 6 DOF humanoid gripper made of lightweight material, similar in size to the human arm, and is able to carry a weight of 1 Kg has been designed and built.